Synergy effect of talent policies on corporate innovation—Evidence from China - Chen, Qiuling; Sun, Ting; Wang, Tianchi (Frontiers in Psychology, 2023)
The talent policy is a powerful tool for the government to implement and the talent is the key resources attributed to corporate innovation. Different types of talent policy instruments need to be synergistically combined to promote corporate innovation. By using the sample of China’s listed companies during the period 2007–2020, this paper applies the multidimensional fixed-effect OLS method to explore the impact of different types of talent policies and talent policy mixes on corporate innovation, and adopts threshold regression model to detect the threshold effect of talent gathering in the framework of government-enterprise interaction. The results are shown as follows: The supply-side talent policy (STP), demand-side talent policy (DTP), and environmental-side talent policy (ETP) all positively affect corporate innovation. Talent policy mixes have a significant synergy on corporate innovation. And the effect of STP- DTP-ETP mixes is greater than that of any two types of talent policy mixes. Talent gathering has a threshold effect on the relationship between STP-DTP-ETP mixes and corporate innovation. Our study provides empirical evidence of the positive impact of different types of talent policy and their mixes on corporate innovation and enriches the literature related to talent gathering.